2020
DOI: 10.3906/kim-2004-50
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, and antibacterial and antioxidant activities of essential oils from Laggeratomentosa Sch. Bip. ex Oliv. et Hiern (Asteraceae)

Abstract: Laggera tomentosa Sch. Bip. ex Oliv. et Hiern (Asteraceae), an endemic Ethiopian medicinal plant is traditionally used to treat various ailments. Previously, the chemical constituents of the essential oil (EO) of its leaves and inflorescence were documented. However, no data about chemical compositions of other parts EOs of the plant have been reported up to date. Moreover, there is no previous biological activity report on any parts EOs of this plant. Thus, in this study, the EOs were isolated from the stem b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…The principal classes of organic compounds in the aerial essential oil were polar and non-polar organic compounds. The chemical composition of this aerial essential oil is different from those reported in other studies for some related species such as those reported for L. tomentosa 42 , L. decurrens 43 , L. aurita 44,45 , L. alata 46 and L. pterodonta 47,48 .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The principal classes of organic compounds in the aerial essential oil were polar and non-polar organic compounds. The chemical composition of this aerial essential oil is different from those reported in other studies for some related species such as those reported for L. tomentosa 42 , L. decurrens 43 , L. aurita 44,45 , L. alata 46 and L. pterodonta 47,48 .…”
Section: Resultscontrasting
confidence: 99%
“…Meanwhile, Bacillus sp and S. dysenteriae were resistance at this concentration of the essential oil. Comparatively, the essential oil investigated in this study showed a promising antibacterial potential than the previously studied species such as Laggera tomentosa where S. aureus and B. cereus showed very low zone of inhibition and E. coli and K. pneumonia showed resistance to the essential oil 54 . The tested bacteria were found to be sensitive to gentamicin (GEN) synthetic antibiotics.…”
Section: In Vitro Dpph Free Radical Scavenging Assaymentioning
confidence: 65%
“…It is worth to note that the activity of C. cernuum APEO against the standard line of E. coli is equal to that against S. aureus, a Gram-positive bacterium. C. cernuum REO was less active against E. coli which conforms to literature data on antibacterial activity of 2,5-dimethoxy- p -cymene-rich essential oils [ 29 , 40 ]. That activity is usually less pronounced against Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 88%
“…& Hiern is frequently being used by the healers to treat tonsils and headache in and around Gullele Botanical Garden. The antioxidant and the bactericidal activities of the essential oil of this plant have been documented ( Getahun et al, 2020 ). The dominant compound in the essential oil of this plant are oxygenated monoterpenes and thymol methyl ether ( Asfaw et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%